Feeding of reindeer calves for slaughtering in the autumn - Jacobsen, Endre; Skjenneberg, Sven (Rangifer, 1981)
Experiments have been carried out for testing the profit of feeding reindeer calves to slaughter maturity in the autumn. The calves were fed a special reindeer calf feed KF-71 (see Table 1 & 2). 16 male calves were fed from September 9th to November 7th. The feed consumption per kg gain in dressed weight was 14,2 kg (estimated to 12,8 fattening feed units). The gain in dressed weight in the period was 5,8 kg per animal. Using the today price of reindeer feed and reindeer meat the feeding in this trial has not been profitable. Some other circumstances which are of importance in estimating the economy by feeding of reindeer calves for slaughter are discussed. Teurastettavien poronvasojen ruokinta syksylla. Abstract in Finnish / Ybteenveto: Poronvasojen ruokinnan kannattavuutta teurastusta silmallapitaen om selvitetty kokeellisesti erityisella tahan tarkoitukseen valmistetulla vakirehulla (taulukot 1 ja 2). Kokeissa ruokittiin 16 vasaa syyskuun 9. ja marraskuun 7. paivan valisena aikana. Rehun kulutus teuraspainon lisayksena saavutettua kiloa kohti oli 14,2 kg. Ruokintajakson aikana teuraspaino lisaantyi elainta kohti 5,8 kg. Kun huomioidaan ruokinnassa kaytetyn rehun hinta ja toisaalta vasanlihan hinta ei ruokinta ollut kannattavaa. Kirjoituksessa pohditaan myos muita suhteita, joilla on merkitysta arvioitaessa teurastettavien poronvasojen ruokinnan taloudellisuutta. Oppforing av reinkalver for slakting om høsten. Abstract in Norwegian / Sammendrag: Det er gjort forsøk for å belyse lønnsomheten ved oppforing av reinkalver til slakt om høsten med et kraftfor laget til dette formål (se Tabell 1og 2). 16 oksekalver ble foret i tidsrommet 9/9 til 7/11. Forforbruket pr. kg tilvekst i slaktevekt var 14,2 kg(beregnet til 12,8 f.f.e.). Tilveksten i slaktevekt i perioden er beregnet til 5,8 kg pr. dyr. Med de priser vi idag har på reinkalvfor og på kalvekjøtt har denne foringen ikke vært regningssvarende. Det er diskutert andre forhold som har betydning for vurdering av økonomien ved oppforing av reinkalv til slakt.